Perubahan Sosial Ekonomi Masyarakat Nelayan Pasca Transmigrasi Daerah di Kampung Teluk Ambun Kabupaten Aceh Singkil - Wardah Muharriyanti Siregar; Rani Putri; Mursyidin Mursyidin (Prodi Sosiologi FISIP Universitas Teuku Umar, 2021)
On December 26, 2004 and March 28, 2005, Aceh experienced an earthquake phenomenon. These two earthquake phenomena caused damage to the Aceh region, including the Aceh Singkil area in Kampung Teluk Ambun. As a result, Teluk Ambun Village, which is in daerah aliran sungai (DAS), had to be moved. Currently Teluk Ambun Village is located in transmigrasi daerah aliran sungai (Trandas) which is in the plantation area. As for the problem in this research is how the socio-economic changes in fishing communities after the occurrence of regional transmigration. The method used is a qualitative research method with a descriptive type. To obtain the data used the method of observation, interviews, and documentation. The results of this study indicate that there are socio-economic changes in fishing communities after regional transmigration, namely changes in fishermen's income, then some fishermen make a shift in their main livelihood, namely as oil palm farmers. In addition, there is a change in the mindset of the fishing community about the importance of education and knowledge, fishermen are paying attention to the education of their children so they can get a good job.